Motorization of traditional craft and its effect on the exploitation of tuna and whitebait anchovy resources at Vizhinjam - Gopakumar, G; Sarma, P S Sadasiva; Velayudhan, A K (Indian Journal of Fisheries, 2011)
The impact of motorization of traditional craft on two fisheries resources, viz. tunas and whitebaitanchovies, was studied. A conspicuous increase in the annual tuna catch was seen from 1984 due to theincreased effort expended by the motorized craft by using more units of drift nets, hooks and lines thannon-motorized craft. The tuna landing increased from 361 tonnes during the pre-motorization period to1976 tonnes during the motorization period. On the contrary, the anchovy landing came down from 580tonnes during the pre-motorization period to 386 tonnes on motorization. A decline was noticed in the effortexpended for whitebait anchovies but the catch rate did not show a steep decline which indicated that thereduction of effort was not due to the decrease in the catch rate. The shifting over of motorized units to driftnet and hooks and lines operation seems to be the major reason for the decline in the effort of boat sieneand nelholi vala which are the main gears for whitebait anchovies